Historical Significance of the Work, Written in Turkish "Tarixi Anbiyo and Hukamo" (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In fact, the genre of prophets is considered the richest and most important genre in the Islamic culture and literature of not only the Arab peoples, but also the Turkic peoples, as it takes its source directly from the Qur'an and hadiths. nourished by the written and oral works, customs and traditions of different peoples. We can see that scholars and poets who were creative in covering the history of Prophets and Prophets were inspired by countless works of historians before them. While writing the article, I would like to give brief information about the role and importance of anbiyo and hukamo genre in the culture, art and literature of the Turkic peoples, as well as dwell on the specific features of this work. works written in Turkish.